Trajectories of Adjustment in a Brazilian Sample of Street-Involved Youth (2019)
Trajectories of adjustment were examined in a sample of street-involved youth across a 1-year period. Participants (N = 113; Mage = 14.18 years; 80.5% male, 91% non-White) were recruited in three Brazilian cities. Interviews conducted at three time points included six measures of physical and psychological adjustment. Unconditional growth models revealed linear declines over time (i.e., improved adjustment) on three indicators: health symptoms, sexual risk behaviors, and negative affect. There were no linear changes in drug use, positive affect, or life satisfaction. Conditional growth models revealed few significant effects for age or gender, but ratings of stressful life events moderated longitudinal changes in health symptoms, drug use, and negative affect. Implications for practice, policy, and theory are discussed. © 2019 Society for Research in Child Development